2021
DOI: 10.3389/fneur.2021.720574
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum Levels of Lactate Dehydrogenase Before Microsurgery Predict Poor Outcome of Aneurysmal Subarachnoid Hemorrhage

Abstract: Introduction: We explored whether higher preoperative serum levels of lactate dehydrogenase (LDH) predicted outcome 3 months after surgery in patients with aneurysmal subarachnoid hemorrhage (aSAH) treated using microsurgical clipping in our institution.Methods: Patients with aSAH treated at our institution between 2010 and 2018 were enrolled. The following parameters were recorded: age, sex, smoking and drinking history, medical history, Hunt–Hess and Fisher grades, aneurysm location, aneurysm size, surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Hunt-Hess grade is used to classify the clinical status of patients with aSAH to select the timing of surgery and determine the prognosis. Related literature has reported that the higher the Hunt-Hess grade of patients at admission, the worse the prognosis ( 26 28 ). Frontera et al showed that in the severe group (Hunt-Hess > 3), patients with aSAH were more prone to ischemic brain injury in the early stage, with higher mortality and disability rates, confirming our findings ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hunt-Hess grade is used to classify the clinical status of patients with aSAH to select the timing of surgery and determine the prognosis. Related literature has reported that the higher the Hunt-Hess grade of patients at admission, the worse the prognosis ( 26 28 ). Frontera et al showed that in the severe group (Hunt-Hess > 3), patients with aSAH were more prone to ischemic brain injury in the early stage, with higher mortality and disability rates, confirming our findings ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are still significant after including other important biomarkers which were not included in previous studies: troponin T, 16,17,23 neutrophil count, 17,23 C-reactive-protein, 16,17 blood glucose, 17 and procalcitonin. 16,17,23 Third, the mortality data are accurate and complete, since death records were extracted from household registration data. 19,20 Fourth, this study also obtained continuous LDH levels for a month after admission, and thus, this study further assessed the impact of trajectory, median, and max LDH levels.…”
Section: Discussionmentioning
confidence: 50%
“…They found that LDH may be a useful biomarker in predicting postoperative pneumonia in patients with aSAH. More recently, in a retrospective cohort of 874 patients who underwent microsurgical clipping, Zheng et al 17 found an association between preoperative serum levels of LDH and mRS outcome at 3 months. The findings showed that a higher preoperative serum LDH level was associated with functional neurological outcomes at 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate dehydrogenase (LDH) is a glycolytic enzyme in brain tissue and can be released from the damaged neuronal cells when the cell membrane is destroyed, which is nonspecific and exists in other human organs, including the liver, heart, skeletal muscle, kidney, and lung. It was reported that LDH could predict the unfavorable outcome of traumatic brain injury [ 12 , 13 , 14 ], intracerebral hemorrhage [ 15 ], and aneurysmal subarachnoid hemorrhage [ 16 ], but few studies assessed the relationship between LDH and the outcome of rIA. Brain tissue hypoxia could be induced by hypophosphatemia because it can promote an adverse increase in hemoglobin oxygen affinity and reduce the oxygen release to the brain [ 17 ], resulting in secondary cerebral hypoxia and brain tissue injury.…”
Section: Introductionmentioning
confidence: 99%